A critical analysis of the creation of separated care structures for unaccompanied refugee minors. (September 2018) - Derluyn, Ilse
Abstract: Unaccompanied refugee minors have been widely recognized as a group of "vulnerable" children and adolescents, in need of special care and reception structures. Equally, in the UN Convention on the Rights of the Child, their specific needs and related rights are stipulated, urging receiving states to ensure unaccompanied children's needs on adequate care services. Yet, the 'specific care and reception structures' that many Western states have created for this growing group of unaccompanied minors are often largely separated from mainstream services within children and youth care, and characterized by other – less – quality norms, in terms of staff ratio, infrastructure, support team, etc. Moreover, more intensive support systems are more and more restricted to "vulnerable" unaccompanied minors, whereby "vulnerability" is related to certain body-related characteristics such as age and gender. Based on an analysis of the evolutions in the way the care structures for unaccompanied minors were set up in Belgium, we critically reflect on the underlying rationales that justify the particularities of these structures, hereby also reflecting about the implications of these rationales for professionals and researchers. Highlights: Care structures for unaccompanied minors are mainly separated systems, different from services for native peers. While age entitles them to care, the separated systems are justified on basis of 'maturity'. The creation of intensive care systems for (extra) vulnerable minors are mainly based on their age and gender. This migration management policy views unaccompanied minors mainly as 'refugees', not as 'children'. This policy also impacts professionals and researchers in this field.